PHYSICAL THERAPY OF MATURE WOMEN WITH ISCHEMIC ACUTE STROKE IN THE LONG-TERM REHABILITATION PHASE: A REVIEW OF MODERN APPROACHES - Павлова, Тетяна; Федусь, Богдана (SWorldJournal, 2026)
The article highlights modern approaches to physical therapy for mature women with ischemic acute cerebrovascular accident in the long-term rehabilitation phase. It analyzes current scientific studies and clinical guidelines that substantiate the effectiv